Mathematical models of hematopoietic reconstitution after stem cell transplantation - Marciniak-Czochra, Anna; Stiehl, Thomas (Model Based Parameter Estimation, 2013)
Transplantation of bone marrow stem cells is a widely used option to treat leukemias and other diseases. Nevertheless this intervention is linked to life-threatening complications. Numerous clinical trials have been performed to evaluate various treatment options. Since there exist strong interindividual variations in patients’ responses, results of clinical trials are hardly applicable to individual patients. In this paper a mathematical model of hematopoiesis introduced by us in(Marciniak-Czochra et al.: Stem Cells Dev. 18:377-85, 2009) is calibrated based on clinical data and applied to study several aspects of short term reconstitution after bone marrow transplantation. Parameter estimation is performed based on the data of time evolution of leukocyte counts after chemotherapy and bone marrow transplantation obtained for individual patients. The model allows to simulate various treatment options for large groups of individual patients, to compare the effects of the treatments on individual patients and to evaluate how the properties of the transplant and cytokine treatment affect the time of reconstitution.